(untitled) (National Administration Journal, 2022)
This article offers a reflection on the concept of social responsibility and shows the results of a survey applied in 2019 to nine of the most renowned Public Relations agencies in Costa Rica, in relation to their practices and the way they plan and measure the results in this field. Likewise, it describes the type of services that are requested by their clients (organizations), what type of initiatives they usually develop and what are the measurement and evaluation parameters.